Puitisasi Terjemahan Al-Qur’an Mohammad Diponegoro (Kajian Kabar Wigati dan Kerajaan: Puitisasi Terjemahan Al-Qur’an Juz ke-29 dan ke-30) - Muhammad Ridha Basri (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2020)
Al-Qur’an was revealed by Arabic which was commonly used in the 7th century. As the spread of Islam to many countries, language transfer of the Qur’an becomes a necessity. In Indonesia, translation began with Tarjuman al-Mustafid in the 17th century. Translation became lively in the 20th century. In addition to translation, poetry translations have also emerged. This study reviews the work of Mohammad Diponegoro, Kabar Wigati dan Kerajaan: Puitisasi Terjemahan Al-Qur’an Juz ke-29 dan ke-30, which was originally published in 1977. This work is in the form of lyric poetry and is classified as a new type of poetry. Diponegoro called his work: the poetic translation of the Qur’an, not the poetic translation as HB Jassin’s work. Mukti Ali called this work as art that was born from the Qur’an. In poetry, words are the key, which connects the reader to the poet’s ideas and intuition. Diponegoro arranges linguistic elements and diction choices like poetry in general. Understanding a poem requires an intensification process. This library research will review the poetry of Diponegoro’s translation of the Qur’an with a historical, literary, hermeneutical-interpretative approach.